Role of Rho in Salt-Sensitive Hypertension - Kawarazaki, Wakako; Fujita, Toshiro (International journal of molecular sciences, 2021)
A high amount of salt in the diet increases blood pressure (BP) and leads to salt-sensitive hypertension in individuals with impaired renal sodium excretion. Small guanosine triphosphatase (GTP)ase Rho and Rac, activated by salt intake, play important roles in the pathogenesis of salt-sensitive hypertension as key switches of intracellular signaling. Focusing on Rho, high salt intake in the central nervous system increases sodium concentrations of cerebrospinal fluid in salt-sensitive subjects via Rho/Rho kinase and renin-angiotensin system activation and causes increased brain salt sensitivity and sympathetic nerve outflow in BP control centers. In vascular smooth muscle cells, Rho-guanine nucleotide exchange factors and Rho determine sensitivity to vasoconstrictors such as angiotensin II (Ang II), and facilitate vasoconstriction via G-protein and Wnt pathways, leading to increased vascular resistance, including in the renal arteries, in salt-sensitive subjects with high salt intake. In the vascular endothelium, Rho/Rho kinase inhibits nitric oxide (NO) production and function, and high salt amounts further augment Rho activity via asymmetric dimethylarginine, an endogenous inhibitor of NO synthetase, causing aberrant relaxation and increased vascular tone. Rho-associated mechanisms are deeply involved in the development of salt-sensitive hypertension, and their further elucidation can help in developing effective protection and new therapies.